2017
DOI: 10.4103/0972-2327.199909
|View full text |Cite
|
Sign up to set email alerts
|

Subjective symptoms of carpal tunnel syndrome correlate more with psychological factors than electrophysiological severity

Abstract: Aim:Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy and is one of the most common requests for electrodiagnosis. We aimed to note the relationship of subjective symptom severity of CTS, with objective electrophysiological severity and psychological status of patients.Patients and Methods:One hundred and forty-four consecutive patients of CTS referred to neurophysiology laboratory of a tertiary care hospital over 1 year were prospectively studied. Boston CTS Assessment Questionnaire (BCTSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…However, this study reported that patients with normal EDX have also the highest HADS depression score in contrast to our study in which depression was not signi cantly correlated with nerve conduction study except for left hand conduction velocity (4). Psychological factors were related to clinical scales but not EDX results in other research studies (6,23). Psychological support should be offered for CTS patients with mild nerve conduction studies in case positive anxiety and depression were found (23).…”
Section: Discussionmentioning
confidence: 67%
“…However, this study reported that patients with normal EDX have also the highest HADS depression score in contrast to our study in which depression was not signi cantly correlated with nerve conduction study except for left hand conduction velocity (4). Psychological factors were related to clinical scales but not EDX results in other research studies (6,23). Psychological support should be offered for CTS patients with mild nerve conduction studies in case positive anxiety and depression were found (23).…”
Section: Discussionmentioning
confidence: 67%
“…There is also increasing evidence supporting a role of psychological factors in CTS . In fact, psychological factors, particularly depression, are more strongly correlated with symptoms than electrophysiological findings in CTS patients . Nevertheless, the role of depression on treatment outcomes is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological factors were related to clinical scales but not EDX results in other research studies (6, 23). Psychological support should be offered for CTS patients with mild nerve conduction studies in case positive anxiety and depression were found (23).…”
Section: Discussionmentioning
confidence: 99%